2014
DOI: 10.1186/s12931-014-0133-y
|View full text |Cite
|
Sign up to set email alerts
|

Conditionally induced RAGE expression by proximal airway epithelial cells in transgenic mice causes lung inflammation

Abstract: BackgroundReceptors for advanced glycation end-products (RAGE) are multiligand cell-surface receptors expressed abundantly by distal pulmonary epithelium. Our lab has discovered RAGE-mediated effects in the orchestration of lung inflammation induced by tobacco smoke and environmental pollutants; however, the specific contribution of RAGE to the progression of proximal airway inflammation is still inadequately characterized.Methods and resultsWe generated a Tet-inducible transgenic mouse that conditionally over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…HMGB1 and its receptor, receptors for advanced glycation end products (RAGE), are both upregulated in alveolar epithelial cells following cigarette smoke exposure (59). Expression of RAGE is also associated with increased lung inflammation (11). It is interesting that the RAGE ligand HMGB1 may inactivate nicotinic acetylcholine receptors in certain neuronal cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 and its receptor, receptors for advanced glycation end products (RAGE), are both upregulated in alveolar epithelial cells following cigarette smoke exposure (59). Expression of RAGE is also associated with increased lung inflammation (11). It is interesting that the RAGE ligand HMGB1 may inactivate nicotinic acetylcholine receptors in certain neuronal cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the level of RAGE in the fixed lung sections, immunohistochemistry was performed by a method described by Bodine et al (27). The paraffin‐embedded sections were cut onto slides at preselected thicknesses of 4–6 μm, dewaxed with xylene, and dehydrated through a series of ethanols of cumulatively increased concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Its mRNA transcript level was increased in vitro in human T cells responding to alloantigen stimulation [24]. e IL-14, IL-17, and TNF-α level in whole lung homogenates were upregulated in RAGE transgenic mice [25]. Helen Kemp et al had demonstrated that the thyroid follicular cells in the thyroid had the ability to express IL-14 mRNA [26].…”
Section: Discussionmentioning
confidence: 99%